Application of the ab initio Theory and PCM–UAHF Model for Prediction of the pKa for Formic and Silanoic Acids Derivatives in Aqueous Solution - REZAEI–SAMETI, MAHDI (Asian Journal of Chemistry, 2010)
Ab initio molecular orbital methods at the CBSEQ level of theory have been used to study the structure and acidity of formic and silanoic acids derivatives in aqueous solution. The calculations are performed at the SCF level with inclusion of SCF–level thermochemical corrections to yield free energies of dissociation, using the basis sets 6- 31G** and the recently parametrized continuum–solvation method PCM–UAHF for the solvation contribution. The model furnishes pKa values in relatively good agreement with experimental data. Scaling different parts of solvation energies provides a significant improvement in results and signifies the importance of balance of individual contributions from electrostatic, cavity, dispersion and repulsion interactions. The result shows that the investigated acids are weak and for C-acids the acidity increases in the order: CCl3COOH > FCOOH > CHCl2COOH > CH2ClCOOH > HCOOH > NO2COOH > CH3COOH > NH2COOH > BrCOOH > ClCOOH; their Si-acidity order is: CCl3SiOOH > CHCl2SiOOH > FSiOOH > ClSiOOH > HSiOOH > BrSiOOH > CH2ClSiOOH > CH3SiOOH > NO2SiOOH > NH2SiOOH.